Who Wants to Work More? Multilevel Study on Underemployment of Working Mothers in 22 European Countries - Milla Salin; Jouko Nätti (MDPI, 2022)
This study examines underemployment of working mothers in 22 European countries. Underemployed mothers are defined as those who wish to work longer hours than they are currently working. Compared to unemployment and employment in general, the research tradition of underemployment is less established. This article contributes to the existing knowledge on underemployment in two ways. First, it focuses on a specific group of workers: mothers. Secondly, while the vast majority of earlier studies has concentrated on single countries, this study is cross-national. Using data from the 2010/2011 European Social Survey (ESS), a multilevel analysis provides three major findings. First, underemployment exists in all countries examined, but the prevalence varies significantly. Second, the prevalence and depth (i.e., how large is the gap between preferred and current working hours) of underemployment are not necessarily correlated; a high prevalence can be accompanied by shallower underemployment and vice versa. Third, at the individual-level, underemployment particularly hurts mothers who are in a more insecure position in terms of their economic and labor market situation. At the country level, underemployment is related to a poorer economic situation and less-extensive childcare system.